Pure Invasive Apocrine Carcinoma of the Breast: A Rare Entity - Sayeedul Hasan Arif; Nazima Haider; Hena A. Ansari; Suhailur Rehman; Mohammad Habib Raza (Middle East Journal of Cancer, 2013)
Pure apocrine carcinoma of the breast is one of the rare variants of invasive breastcarcinoma. Significant research has been conducted on cases of apocrine carcinoma,and the results may help in development of new therapies and assessing prognosis. Wehereby present a case of pure invasive apocrine carcinoma in a 50-year old female, witha short review of recent developments with regard to this lesion.